The Neglected Group: Cognitive Discourse Markers as Signposts of Prosodic Unit Boundaries - Simona Majhenič; Mitja Beras; Janez Križaj (Languages)
The present paper examines and compares the role of cognitive discourse markers (DMs), such as uhm, like, or I mean, and a set of prosodic parameters as indicators of prosodic boundaries. Cognitive DMs traditionally are not studied as a separate DM group on par with the ideational, sequential, rhetorical, or interpersonal group. However, as they reflect the speaker’s mental processes during speech production, they offer an exceptional glimpse into how speakers construct their verbalisations. Along with the analysis of DMs, prosodic parameters, including pitch and intensity reset, speech rate change, and pauses, were automatically annotated to determine how well they overlapped with the manually annotated prosodic boundaries. To accommodate for the natural variability in speech, the parameters were evaluated using relative comparison methods. Among the prosodic parameters, pauses were found to overlap most often with the manually annotated prosodic boundaries. Cognitive DMs in the function of realising new information, restructuring, and emphasis indeed proved as relevant boundary indicators, however, the group of cognitive DMs as a whole fell behind the group of sequential and rhetorical DMs, which overlapped most frequently with the manually annotated prosodic boundaries.